Hubungan Kepribadian Extraversion Dengan Perilaku Agresif Remaja Pengguna Game Online - Reynaldo Yogi Siswoko; Defi Astriani; Alaiya Choiril Mufidah (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA BLITAR, 2023)
Online game that contain element of violence and can be play multiplayer can trigger emergence of aggressive behavior especially for teenagers who use online games. The purpose of this study is to know is there a relationship between extraversion personality and aggressive behavior of adolescent who use online games. This research method is correlational with a quantitative approach. The number of subjects is 95 people were taken using a purposive sampling technique with criteria 1) adolescent 13-21 years old, 2) domiciled in Blitar 3) users of online game mobile legends, free fire, PUBG, and genshin impact. Numerical data analysis was processed using statistical methods using the IBM SPSS Statistics 21 application. The results of the research data analysis showed a significance value of t > 0.05 with a value of r > 0.5. So it can be conclude that there is a significant relationship between extraversion personality with aggressive behavior with a negative correlation direction which means if the higher individual’s extraversion personality type, the lower the aggressive behavior. Conversely, if the lower individual's extraversion personality type, aggressive behavior will tend to be high.